2017
DOI: 10.1016/j.jvolgeores.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of volcanic unrest on high-temperature fumaroles by satellite thermal monitoring: The case of Santa Ana volcano, El Salvador

Abstract: Soil CO2 flux and 222Rn activity measurements may positively contribute to the geochemical monitoring of active volcanoes. The influence of several environmental parameters on the gas signals has been substantially demonstrated. Therefore, the implementation of tools capable of removing (or minimizing) the contribution of the atmospheric effects from the acquired timeseries is a challenge in volcano surveillance. Here, we present four years-long continuous monitoring (from April 2007 to September 2011) of rado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
0
22
0
1
Order By: Relevance
“…On active volcanoes, temperature appears as one of the most intuitive parameter to look for precursors of major or paroxysmal eruptive activity. This parameter can be measured directly by temperature sensors inserted into the soil (Friedel et al, 2004;Ricci et al, 2015;Gaudin et al, 2017) or by remote sensors (Wright et al, 2004;Coppola et al, 2015a;Laiolo et al, 2017). Thermal anomalies recorded on active volcanoes can be subdivided into two groups depending on how the heat transfer is directed toward the surface:…”
Section: General Contextmentioning
confidence: 99%
“…On active volcanoes, temperature appears as one of the most intuitive parameter to look for precursors of major or paroxysmal eruptive activity. This parameter can be measured directly by temperature sensors inserted into the soil (Friedel et al, 2004;Ricci et al, 2015;Gaudin et al, 2017) or by remote sensors (Wright et al, 2004;Coppola et al, 2015a;Laiolo et al, 2017). Thermal anomalies recorded on active volcanoes can be subdivided into two groups depending on how the heat transfer is directed toward the surface:…”
Section: General Contextmentioning
confidence: 99%
“…Moreover, the use of Thermal InfraRed (TIR) satellite sensors is also a consolidated technique [10][11][12][13][14][15][16] for monitoring the volcanic activity at different spatial resolutions: low (e.g., Meteosat Second Generation, MSG, or the Geostationary Environmental Satellite, GOES), moderate (e.g., MODIS, AVHRR, Sentinel 3) and high (e.g., Advanced Spaceborne Thermal Emission and Reflection Radiometer, ASTER, and Landsat 8) [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The development of remote sensing techniques aimed at the estimation of surface temperatures of lava flows, lava lakes, and domes, as well as fumaroles of active volcanic areas, has allowed significant improvements in volcano monitoring activity [6,[31][32][33][34]. Indeed, recent studies have shown thermal anomalies as an indicator of change in volcanic systems [4,35].…”
Section: Introductionmentioning
confidence: 99%
“…1a) is a land of volcanoes, being located within the volcanic belt known as Central American Volcanic Front (CAVF) that extends from Guatemala to Costa Rica and is related to the subduction of the Cocos Plate beneath the Caribbean Plate (Corti et al, 2005;Agostini et al, 2006 and references therein). In El Salvador, many lakes are associated with volcanic systems, considered as quiescent or showing moderate hydrothermal activity (Alegria, Apastepeque, Aramuaca, Cuscachapa, Coatepeque, Ilopango, Verde lakes; Rouwet, 2013), or characterized by strong fumarolic emissions (Lake Santa Ana; Bernard et al, 2004;Hernández et al, 2007;Scolamacchia et al, 2010;Colvin et al, 2013;Laiolo et al, 2017). This work focuses on Lake Coatepeque (close to Santa Ana Volcano) and Lake Ilopango (inside the Ilopango Caldera) ( Fig.…”
Section: Introductionmentioning
confidence: 99%